DESAIN LAPORAN KEUANGAN BERBASIS MICROSOFT EXCEL PADA UMKM - SeptianaMS03; Sugiono; Tukasno (Jurnal Peduli : Jurnal Pengabdian Kepada Masyarakat, 2022)
The goal of this study is to arm MSME stakeholders with information and understanding so they can grow MSMEs by embracing technology. In some circumstances, this causes fresh issues when making judgments down the road. Microsoft Excel is a handy tool for modern financial reports that makes it simpler to record transactions for a certain time period. It is envisaged that by using this application, MSME players will stop manually recording reports, making it simpler for outsiders and MSME actors to view financial data. This study uses participatory action research as its methodology (PAR). Additionally, the outcomes of this study are through conducting training on the design of financial reports based on Microsoft Excel to assist MSME actors in making them.